DETERMINING THE MARKET LEADER OF CELLULAR PHONE USING ANALYTICAL HIERARCHY PROCESS (AHP) AT SMARTPHONE ANDROID IN MANADO - Kondoy, Fandy F. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The cellular-phone market in Manado is fairly competitive. Two of the most well-known are Samsung and Sony. The cell phone has influenced society and culture in ways that make life easier and more controllable. The objectives of this research are to identify the market leader of cellular phone in Manado using Analytical Hierarchy Process, and to analyze the key strengths of each cellular phone brand. To achieve these objectives, expert opinions are analyzed as data. These data are analyzed by using analytical hierarchy process. Theories supporting this research are marketing, market, market leader, and marketing mix.Â  The population in this research is people who use this two of cellphone (Samsung and Sony) with sample as many as 100 respondents. Result and conclusion are Samsung is the market leader of cellular-phone market in Manado since it got the highest average weight during the result of analyzes and computation of expert opinion. In the future, Samsung needs to improve their product innovation and technology to maintain their position as a market leader, because cellular-phone competition is really tight. Samsung smartphone products are more common for people in the Manado City, compared with the similar ones for Sony. And finally, Samsung became the Market Leader for the cellular phone in Manado city for a certain period. Keywords: market leader, cellular phone